Decentralised Job Matching - Guillaume Haeringer; Myrna Wooders (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper studies a decentralised job market model where firms (academic departments) propose sequentially a (unique) position to some workers (Ph.D. candidates). Successful candidates then decide whether to accept the offers, and departments whose positions remain unfilled propose to other candidates. We distinguish between several cases, depending on whether agents' actions are simultaneous and/or irreversible (if a worker accepts an offer he is immediately matched, and both the worker and the firm to which she is matched go out of the market). For all these cases, we provide a complete characterization of the Nash equilibrium outcomes and the Subgame Perfect equilibria. While the set of Nash equilibria outcomes contain all individually rational matchings, it turns out that in most cases considered all subgame perfect equilibria yield a unique outcome, the worker-optimal matching.
Keywords: C78; C62; J41; 330; Two-sided matching; Job market; Subgame perfect equilibrium; irreversibilities; Suchtheorie; Dynamisches Spiel; Theorie; Matching